Analisis Pengaruh Getaran Peledakan Terhadap Kestabilan Lereng Lowwall Pada Pit 1 Tambang Batubara PT Atha Marth Naha Kramo (AMNK) Jobsite Langap, Kabupaten Malinau Propinsi Kalimantan Utara - Muhamad Supardi; Supandi Supandi; R. Andy Erwin Wijaya (MINERAL, 2021)
PT. Atha Marth Naha Kramo is a coal mining company located in Langap Village, South Malinau District, Malinau Regency, North Kalimantan, the purpose of this study was to determine the effect of blasting vibrations on lowwall slopes, to determine the probability of avalanches affected by blasting vibrations. In the study the analysis method used the Monte Carlo probability method and the method used to calculate vibrations with the regression approach and the actual condition of the slope was divided into three sections. Obtained regression equation for predicted value at slope point PPA = 4.0512 (SD)-1.238, for amax value (horizontal acceleration) at the slope point using equation amax = 0.6339 (PPA) - 0.0031, this equation is close to the recommendation of Marcusson with amax of 1/3 and 1/2 of the value (PPA). From the results of the analysis of the effect of vibration on the stability of the slope in section A-A safe conditions, section B-B unsafe conditions, section C-C unsafe conditions. So, in the study recommended a safe slope geometry. For all sections with an overall height between 32 - 51meter and overall slope 33°-39°, height 10meter and width of 5 meters, and vibration safe limit in section A-A is 0.275 g, section B-B 0.152g, section C-C 0.188g.